Análisis de la recuperación de la cartera vencida del Banco Nacional de Fomento sucursal La Maná, año 2014 - Sarabia Mariño, Diana Carolina (2015)
The purpose of the project is to analyze how the recovery of overdue loans Banco Nacional de Fomento Sucursal La Maná is being processes and policies recovery credit and collection department the main focus of study, then the causes of maturity is determined lending operations. The process used to assess the recovery of performing loans applied in the institution, including all actions of this area, in order to secure and protect their resources by ensuring the effectiveness and reliability of recovery Manágement with strict compliance with laws, regulations and standards set by the bank. In this research project a thorough study of recovery Manágement is developed; revision of laws, regulations, rules, procedures manual, which serves as a basis for obtaining alleged deficiencies or irregularities identified as a result of the implementation of recovery procedures. It being based on the results of research recommendations are raised to mitigate the problems afflicting the credit department and collection of the Nacional de Fomento Sucursal La Maná, the results will be announced to the head of area for further monitoring, making it improve Manágement significantly.